Between Hobbes and Spinoza. Research on the Philosophical Matrix of Ferdinand Tönnies’ Sociological Categories - Furio Ferraresi (Scienza & Politica, 2017)
This essay reconstructs the main lines of Ferdinand Tönnies’ (1855-1936) critical approach to the thought of Hobbes and Spinoza. Specifically it shows the role played by the two philosophers in developing the categories of community (Spinoza) and society (Hobbes). From the stand point of political thought, the essay reveals how Tönnies’ on going interpretation of Hobbes focuses more and more on the constitutive moment of the modern form of State. In this area it draws on Spinoza’s reflections on democracy as an absolutum omnino imperium. Tönnies is thus able to distinguish conceptually between the Hobbesian State, as a “society” that absorbs all natural law, and its natural law origin (the «original assembly»), where we find a “common” element that can never be entirely neutralized by the State.